PERAN REHABILITASI MEDIS DALAM PEMULIHAN COVID-19 - Yelvi Levani; Gusti Ratu Az-zahra; Imaduddin Ahmad Hakim; Zia Azizah Neurinda Mochtar; Cantika Budiawan; Muhammad Enal Elfansyah (PROCEEDING UMSURABAYA, 2023)
Patients after COVID-19 most often complain of symptoms that are still experiencinghead pain, joint pain, shortness of breath, poor sense of smell, feeling chest palpitations,feeling tired quickly, feeling excessive fear and anxiety. So, the role of rehabilitation is verymuch needed in an orderly,structured, systematic, and planned system by directions andrecommendations from doctors so that the residual symptoms of COVID-19 outbreak do notcause symptoms again so that patients can carry out normal activities as before. The dataand research we are looking for on medical COVID-19 recovery in rehabilitation is stilldifficul to obtain because there are still few sources. On the other hand, the COVID-19pandemic is a new event around the beginning of 2020.Keywords: symptom, COVID-19, infection rehabilitation, therapy